ChemInform Abstract: Structural, Transport, Magnetic and Magnetoelectric Properties of CaMn1‐xFexO3‐δ (0.0 ≤ x ≤ 0.4). Issue 30 (July 2015) - Singh, Brajendra
Abstract Polycrystalline CaMn1‐xFexO3‐δ (x = 0—0.4) manganites are prepared by calcination of stoichiometric amounts of CaCO3, MnO2, and Fe2O3 (950 °C, 2 d) followed by sintering in air (1300 °C, 1 d).